The Impact Of Energy Consumption On Environmental Degradation And Economic Growth In Syria 1970 – 2012 - Hayyan, Waked (2022)
The main issues of the study are how to improve energy consumption, reduce environmental degradation and increase economic growth. Hence, this study attempts to investigate the causal nexus between energy consumption, environmental degradation and economic growth in Syria. This study utilises the VAR model, ADF unit root test, Johansen cointegration test, granger casualty test, impulse response function and variance decomposition analysis.